Muslim rulers and rebels : everyday politics and armed separatism in the southern Philippines - McKenna, Thomas M., 1952- (Berkeley : University of California Press, 1998)
In this account of the Muslim separatist rebellion in the Philippines, Thomas McKenna challenges prevailing anthropological analyses of nationalism as well as their underlying assumptions about the interplay of culture and power. He examines Muslim separatism against a background of more than four hundred years of political relations among indigenous Muslim rulers, their subjects, and external powers seeking the subjugation of Philippine Muslims.
Introduction Extraordinary and Everyday Politics in the Muslim Philippines -- Chapter 1 The Politics of Heritage -- Chapter 2 People and Territory in Cotabato -- Chapter 3 Islamic Rule in Cotabato -- Chapter 4 European Impositions and the Myth of Morohood -- Chapter 5 America's Moros -- Chapter 6 Postcolonial Transitions -- Chapter 7 Muslim Separatism and the Bangsamoro Rebellion -- Chapter 8 Regarding the War from Campo Muslim -- Chapter 9 Unarmed Struggle -- Chapter 10 Muslim Nationalism after Marcos -- Chapter 11 Resistance and Rule in Cotabato.
Includes bibliographical references (pages 339-353) and index.
Print version record.
English.
JSTOR
Keywords: Moro National Liberation Front; Moro National Liberation Front; Cotabato City Region (Philippines) -- Politics and government; Muslims -- Philippines -- Cotabato City Region; Mindanao Island (Philippines) -- History -- Autonomy and independence movements; Muslims -- Philippines -- Mindanao Island -- Politics and government; Mindanao (Philippines : Île) -- Histoire -- Autonomie et mouvements indépendantistes.; HISTORY; SOCIAL SCIENCE / Anthropology / Cultural & Social; Autonomy and independence movements; Muslims; Muslims -- Politics and government; Politics and government; Philippines -- Cotabato City Region; Philippines -- Mindanao Island; East Asia; Regions & Countries - Asia & the Middle East; History & Archaeology; History